MEASURING NOISE LEVEL IN THE TEXTILE INDUSTRY - CLAUDIA TOMOZEI; ALEXANDRA PIPA; OANA IRIMIA; MIRELA PANAINTE-LEHADUS; FLORIN NEDEFF (Journal of Engineering Studies and Research)
The Company SС Sonomа Trаding currently owns a production area, the activity being carried out on a placement has a built area of 275 m2. The monitoring of the noise level within the company Sonoma Trading SRL was carried out for three weeks, between 18.05.2015 - 5.06.2015; for the noisiest equipments. Result of noise level was in the range 82.41 dB – 63.73 dB. The background noise was 38.59 dB. Based on the results of the measurements made, the noise map for both tailoring rooms was prepared: the tailor room and the ironing - stapled - packing section. According to the obtained results, the noise level values within the company Sonoma Trading SRL do not exceed the maximum allowed imposed by the legislation in force.